The Effect of E-commerce on People's Buying Interest in Traditional Markets - Nurazila; Decky Hendarsyah; Eryana (Universitas Airlangga, 2023)
Background: Traditional markets are essential to many people for shopping and fulfilling their daily needs is necessary to study people’s purchase behavior, especially regarding purchase interest, in an era of increasingly advanced technological developments including e-commerce. Objective: This study aims to show the effect of e-commerce on people’s purchase interest in traditional markets. Method: This type of study is descriptive and quantitative, with primary and secondary data sources. The primary data is taken from questionnaires and interviews, while the secondary data is taken from some literatures. The population of the study is the people of Bengkalis Regency, Riau Indonesia in amount of 564,689 people in total. This study used random sampling. The sample measurement technique uses the Slovin approach and obtained a total of 400 respondent and for the data analysis, this study used simple linear regression. Results: The results of the study show that e-commerce positively and significantly affects people’s purchase interest in traditional markets. Conclusion: E-commerce positively and significantly affects the purchase interest of the Bengkalis people in traditional markets as much as 66.1% and the rest 33.9% is affected by other factors. Nevertheless, most people only use e-commerce as a catalogue to gain new information about a product, their purchase interest remains mostly buying the product in traditional markets. This study will theoretically enrich the previous existing theories and practically becomes a reference for business-persons to increase people’s purchase interest. Keywords: purchase interest; buying interest; purchase intention; e-commerce; traditional market